Kemampuan Berpikir Kreatif Matematis Siswa melalui Model Pembelajaran Brain-Based Learning - Cut Ardhilla Putri; Said Munzir; Zainal Abidin (Didaktik Matematika, 2019)
The students' mathematical creative thinking ability is still low and lacks attention in the implementation of mathematics learning. This issue requires an attempt to address the problem. One of the efforts that can be done by teachers to develop creative thinking ability is by applying a Brain-Based Learning model of learning. This study aims to describe the development of students' mathematical creative thinking ability through Brain-Based Learning model. This research employed a qualitative approach. Participants were six students selected from 30 students of class VIII-1 in SMP Negeri 19 Percontohan Banda Aceh. The instruments used in this research are creative thinking ability test and interview guide. The results showed that the ability of students' mathematical creative thinking through Brain-Based Learning model developed. The development of students' creative thinking ability in each indicator is different. The students' mathematical creative thinking abilities for indicators of fluency and flexibility develop at each session. For indicators of originality and elaboration, there was a decrease in the second session but increased for the next one.